Smart tourism – City tourism radar - Lobao, Filipa (2022)
Lobao, F., de Castro Neto, M., & Aparicio, M. (2019). Smart tourism – City tourism radar: A tourism monitoring tool at the city of Lisbon. In Atas da Conferencia da Associacao Portuguesa de Sistemas de Informacao 2019: 19ª Conferencia da Associacao Portuguesa de Sistemas de Informacao, CAPSI 2019 [19th Conference of the Portuguese Association for Information Systems, CAPSI 2019], Lisboa; Portugal; 11 October 2019 through 12 October 2019 (Atas da Conferencia da Associacao Portuguesa de Sistemas de Informacao). Associação Portuguesa de Sistemas de Informação.